(1590) socioeconomic aspects of economic reform policies in Egypt الجوانب الاجتماعية والاقتصادية لسياسات الإصلاح الاقتصادي في مصر - khalifa, magdi (The Institute Of National Planning., 2018)
Reform initiatives in developing countries have typically taken one of two forms: repeated attempts to improve the existing system of planning and management or moving towards a market oriented system. The latter group of countries emphasized greater price flexibility, fewer controls on inputs.